Outcome of a Multi-modal CBT-based Treatment Program for Chronic School Refusal - Johan Strömbeck PhD Student; Robert Palmér BA; Ia Sundberg Lax BA; Jonas Fäldt MA; Martin Karlberg PhD; Martin Bergström PhD (SAGE Publishing, 2021)
School refusal (SR) can have several negative consequences, but effective treatments are available. When chronic, school absence requires comprehensive treatment. This study evaluates an intervention for SR based on a Cognitive Behavioral Therapy (CBT) model, Hemmasittarprogrammet (HSP). Attendance, anxiety, depression, quality of life, and emotional and behavioral symptoms were measured at pre-treatment, post-treatment, and follow-up. The participants (n = 84; 69% male) were SR students between 10 and 17 years old and their parents. School attendance increased after treatment and at follow-up. The proportion of students totally absent from school decreased and the number of students with an acceptable level of school attendance increased. Levels of anxiety and depression were lower both post-treatment and at follow-up for the youths and their parents. HSP, a promising treatment program for school refusal, builds on the literature of CBT-based programs, which has been shown to be effective for SR treatment. However, more research about the effectiveness of the program is needed. Future studies should have a stronger research design, include a measure of fidelity, and be evaluated independent of the founders of the program under investigation.